In the field, among the feathered a history of birders & their guides - Dunlap, Thomas R. 1943- (Oxford University Press, 2011)
America is a nation of ardent, knowledgeable birdwatchers. But how did it become so? And what role did the field guide play in our passion for spotting, watching, and describing birds? This book tells the history of field guides to birds in America from the Victorian era to the present, relating changes in the guides to shifts in science, the craft of field identification, and new technologies for the mass reproduction of images.